1975
DOI: 10.1111/j.1432-1033.1975.tb21032.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of Tyrosyl Residues in Human α‐Lactalbumin

Abstract: a-Lactalbumin isolated from human milk was reacted with tetranitromethane in molar excess of 8 -32 mol/mol of tyrosine. After gel filtration on Sephadex G-75, followed by chromatographic fractionation using DEAE-Sephadex A-25, three main components were separated, which differed from one another in the extent of nitration.These protein fractions were found to contain, respectively, one and two nitrotyrosine residues, or two nitrotyrosine residues together with one nitrotryptophan. The lactose synthase specifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
(1 reference statement)
1
2
0
Order By: Relevance
“…One or two tyrosines in -lactalbumin were known to be unreactive with cyanuric fluoride or with iV-acetylimidazole, which may be consistent with the present results (Gorbunoff, 1967;Kronman et al, 1971). Prieels et al (1975) have suggested that Tyr-103 in human -lactalbumin, in which all the tyrosines occupy the same positions as in bovine a-lactalbumin, is more easily nitrated than Tyr-18 and that these two residues are more exposed than Tyr-36 and -50. The results are also consistent with the assignment in Table I.…”
Section: Discussionsupporting
confidence: 91%
“…One or two tyrosines in -lactalbumin were known to be unreactive with cyanuric fluoride or with iV-acetylimidazole, which may be consistent with the present results (Gorbunoff, 1967;Kronman et al, 1971). Prieels et al (1975) have suggested that Tyr-103 in human -lactalbumin, in which all the tyrosines occupy the same positions as in bovine a-lactalbumin, is more easily nitrated than Tyr-18 and that these two residues are more exposed than Tyr-36 and -50. The results are also consistent with the assignment in Table I.…”
Section: Discussionsupporting
confidence: 91%
“…Other possible modifications that were investigated included nitrotryptophane, 36 nitrophenylalanine, 37 hydroxyphenylalanine, 37 nitrohistidine, 35 and conversion of sulfhydryl to sulfenic and sulfonic acid in cysteine. 38 The mass spectral data did not show evidence for any of these modifications.…”
Section: Discussionmentioning
confidence: 99%
“…teins (43). Chemical nitration of functionally important tyrosine residues by tetranitromethane was often found to inactivate or alter the properties of the enzyme under investigation (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%